Low glycemic index rice-a desired trait in starchy staples - Jukanti, Aravind Kumar; Pautong, Putlih Adzra; Liu, Qiaoquan; Sreenivasulu, Nese (Elsevier, 2020)
The global shift in food consumption patterns accompanied by a sedentary lifestyle has been driving the upsurge of non-communicable diseases, projected to remain as a global health challenge for the coming decades. Sustainable food-centric interventions should be developed and strengthened to mitigate the growing health concerns with huge socio-economic implications. Milled white rice is typically starch-rich, serves as the major daily caloric source for a majority of the world population especially in Asia. Most rice varieties are of high glycemic index (GI), a food quality inferenced to contribute to the health problems surrounding high-calorie intake and dysregulated glucose metabolism. Manipulation of GI through various approaches will significantly help in the fight against diabetes and related diseases. A multidisciplinary approach of (a) introducing low to moderate GI property to modern varieties of rice through genetic manipulations, and (b) diet-based diversification solutions in a healthy plate of well-balanced portions of macronutrients with low GI food matrix together with elevated nutrient density and dietary fibre (DF) offers a sustainable solution to address the growing concern in meeting double burden nutritional challenges.